151 The Impact of the 2006 Massachusetts Healthcare Reform on Neurosurgical Procedures and Patient Insurance Status. (August 2015) - Villelli, Nicolas W.; Das, Rohit; Yan, Hong; Zou, Jian; Barbaro, Nicholas M.
Abstract : INTRODUCTION: The Massachusetts Healthcare Policy of 2006 has many similarities to the Affordable Care Act (ACA). There are concerns the ACA will negatively impact case volume and reimbursement for physicians. Analyzing neurosurgical cases and patient insurance status before and after the Massachusetts policy change can provide insight into the future of neurosurgery in the American health care system. METHODS: The Massachusetts State Inpatient Database, which provides demographic information on hospital discharges, was studied for all neurosurgical International Classification of Diseases, Ninth Revision (ICD-9) procedure codes from 2001 to 2012. Four categories of ICD-9 codes were created: Tumor, Other Cranial/Vascular, Shunts, and Spine. A comparison of case totals and uninsured cases, before and after the policy change, was performed. Data from New York were used as a control. RESULTS: After 2008, there was a decrease in uninsured cases in all 4 categories in Massachusetts. The number of cases for Tumor and Spine were unchanged, while Other Cranial/Vascular increased. Shunt totals decreased postpolicy, but exhibited a similar trend to the control. For New York, Spine case total and uninsured case volume increased, while Other Cranial/Vascular case totals decreased. CONCLUSION: After the Massachusetts Healthcare Reform, the number of uninsured individuals undergoing surgeries significantly decreased for all categories of neurosurgical procedures, but more importantly, the total number of cases did not change dramatically. To the extent that Massachusetts predicts the overall US experience, some aspects of reimbursement may be positively impacted by the ACA. Neurosurgery, which treats patients with more urgent conditions, may be affected differently than other specialties.